To study the bone mineral density and vitamin D in patients suffering from rheumatoid arthritis irrespective of duration in comparison to age and sex-matched controls who were not having any musculoskeletal disorder - Bhimwal, Raj Kumar; Makwana, Mohan; Sanawadiya, Harish; Bhati, Ratan Lal (International Journal of Advances in Medicine, 2017)
Background: Rheumatoid arthritis is a chronic inflammatory disease of synovial tissue of joints of unknown etiology marked by a symmetric, peripheral, polyarthritis. Osteoporosis is a progressive systemic skeletal disease characterised by reduced bone mass/density and micro-architectural deterioration of bone tissue. Osteoporosis is more common in patients with rheumatoid arthritis than an age and sex-matched population. Chronic use of glucocorticoids and disability-related immobility also contributes to osteoporosis. Methods: The present study was conducted at Department of Medicine, Dr. S. N. Medical College, Jodhpur, India. Case control study was conducted to determine bone mineral densities (BMD) and vitamin D levels among patients with rheumatoid arthritis attending the medicine OPD and IPD, Dr. S. N. Medical College, Jodhpur, Rajasthan, India. 25 patients with rheumatoid arthritis and 25 age and sex-matched controls were studied. All known cases of Rheumatoid Arthritis attending Medicine outdoor and patients who are admitted indoor. Patients with co-morbidities like diabetes mellitus, coronary artery disease, hypertension, chronic kidney disease and pre-existing osteoporosis. Results: Mean age of the study population was 49.68±8.4 yrs; most of the subjects were females. Vitamin D levels were found to be comparatively lower in females. Vitamin D deficiency was more prevalent of in urban population. As the age increased the levels of vitamin D and BMD decreased. Inadequacy in vitamin D levels was more prevalent in Rheumatoid arthritis patients, 74.99% females had low BMD values. Correlation of low BMD with RA was statistically significant. The duration of Rheumatoid arthritis was related to vitamin D levels significantly (p<0.013). The longer the duration of disease more number of RA patients had vitamin D deficiency. All patients with RA for more than 4 years had osteoporosis. The duration of Rheumatoid arthritis was related to low BMD significantly (p<0.025). The correlation of HAQ (health assessment questionnaire) with BMD is statistically significant; the correlation of DAS score with RA duration is statistically significant. The correlation of DAS score with BMD is statistically significant. The lesser the BMD more number of RA patients had moderate or severe scores. Conclusions: Vitamin D levels were found to be comparatively lower in females especially in urban areas. Vitamin D deficiency and low BMD is more prevalent in Patients of rheumatoid arthritis in comparison to controls. High index of suspicion is required during follow-up of rheumatoid arthritis patients.